(untitled) (Acta Scientiarum. Biological Sciences, 2011)
A female specimen of choicy ruff, Seriolella porosa, is reported for the first time in Brazilian waters, 384 mm total length captured by the bottom trawl commercial fishery on August 12th, 2007, at 36 meters local depth off the São Paulo coast, southeastern Brazil (23º49’56’’S; 45º53’24’’W). The occurrence may be uncommon, probably associated with a branch of cold water of the Malvinas current.